A high-throughput model system for investigating carotenoid biogenesis in plant via callus culture - Othman, Rashidi; Mohd Zaifuddin, Fatimah Azzahra; Mohd Hassan, Norazian (2015)
This study aimed at establishing callus cultures as an alternative research tool to study the regulatory mechanisms of the carotenoid biosynthesis in plant through a controlled environment. Previous studies established that selasih or O. basilicum is rich with carotenoids such as neoxanthin, lutein, violaxanthin, α-carotene and ß-carotene. Interestingly other researcher found selasih was rich with high amount of zeaxanthin. Therefore the question remain in this study is what are the key factors regulate carotenoid accumulation mechanism and how far the extent of environmental and genetic influences on plant carotenoid biosynthesis. In this study carotenoid biogenesis will be investigated in selasih callus, pumpkin and Geroda cultures as a potential model system for rapid initiation, extraction and analysis of carotenoids by providing stringent control of genetic, developmental and environmental factors. The value of this experimental system for investigating variables controlling carotenoid accumulation is then tested by assessing the effects of environmental variables, such as drought stress, light intensity and water stress on carotenoid accumulation. Reversed phase high-performance liquid chromatography (HPLC) analysis established that light, salicylic acid and PEG influenced the presence of lutein and β-carotene. Although these factors had an effect on the carotenoid content and profile, the most influential factor appeared to be plant species selection. This study is expected to provide new knowledge on the key factors involved in regulatory mechanisms of individual carotenoid biosynthesis in a particular biology system of plant. On top of that, future exploration and manipulation of the genetic make-up is made possible to enhance or enrich certain individual carotenoid in food crops without altering the genes or genetic modification.